De novo discovery of a tissue-specific gene regulatory module in a chordate - Johnson, David S.; Zhou, Qing; Yagi, Kasumi; Satoh, Nori; Wong, Wing; Sidow, Arend

(untitled) (Genome Research, 2005)
We engage the experimental and computational challenges of de novo regulatory module discovery in a complex and largely unstudied metazoan genome. Our analysis is based on the comprehensive characterization of regulatory elements of 20 muscle genes in the chordate, Ciona savignyi. Three independent types of data we generate contribute to the characterization of a muscle-specific regulatory module: (1) Positive elements (PEs), short sequences sufficient for strong muscle expression that are identified in a high-resolution in vivo analysis; (2) CisModules (CMs), candidate regulatory modules defined by clusters of overrepresented motifs predicted de novo; and (3) Conserved elements (CEs), short noncoding sequences of strong conservation between C. savignyi and C. intestinalis. We estimate the accuracy of the computational predictions by an analysis of the intersection of these data. As final biological validation of the discovered muscle regulatory module, we implement a novel algorithm to search the genome for instances of the module and identify seven novel enhancers.